Conveyance Properties of Subsurface Stormwater Module - Charles Hin Joo, Bong; Leonard Lik Pueh, Lim; Chee Khoon, Ng; Siew Liang, Chai; Fang Yenn, Teo; Sai Hin, Lai; Frederik Josep, Putuhena (Semarak Ilmu Publishing, 2025)
Subsurface stormwater module is one of the components of a sustainable drainage system as recommended by Urban Stormwater Management Manual for Malaysia. Existing subsurface stormwater module in the literature are either suited for storage (higher roughness) or to convey flow (lower roughness). The current study was conducted to evaluate the conveyance properties for a new stormwater module design that is suited for both storage or conveyance purposes. The experiment was set up in the laboratory using a rectangular flume to determine the conveyance capability in terms of the flow retardation and roughness coefficient Manning’s n value. Results from the experiment have shown that installation of the new stormwater module design can cause reduction in the mean discharge between 2.50% to 9.09%. The Manning’s n values were found to range between 0.027 and 0.064 which falls within the mid-range value of existing literature. This implies the suitability of the new stormwater module design for both detention and subsurface conveyance purposes.